Collaborative dialogue with student teachers as a follow-up to teacher in-service education and training - (:unkn) unknown (My University, 2004)
This study evaluates the success of collaborative dialogue between students and co-operating teachers as a follow-up to in-service education and teaching (INSET). Current INSET programmes are on the whole found to be insufficient due to the fact that they do not provide the participant teachers with opportunities to reflect on their own experiences, NA. The qualitative and quantitative results of this study show that taking part in a collaborative dialogue with student teachers following INSET impacts positively on the professional development of participating teachers. This may help to resolve the problems and difficulties associated with INSET programmes in general. © 2004, Sage Publications. All rights reserved.